Akibat Hukum Akta PPAT yang Dipalsukan oleh Pegawai Kantor PPAT: Studi Kasus Putusan PN Mataram Nomor 16/Pid.B/2018/PN Mtr - Ritonga, Rina Yozarni; Purba, Hasim; Suhaidi; Suprayitno (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
A deed is one of the most important documents that must be present when someone claims that an item, whether movable or immovable, is truly owned by that person. In land ownership, a deed cannot be removed, therefore a deed is made to obtain proof of legal ownership. In this case, deeds are made by Land Deed Making Officials who have been sworn in to carry out their profession so that they do not deviate from their profession, but some Land Deed Making Officials often deviate and even falsify the land deeds they make. In this thesis, we will discuss the basics of the legal process and what the status of the deed made is in the law. Not only that, this thesis will also discuss how the Land Deed Official receives the consequences under the applicable law. This research uses the Normative Juridical method with an approach to Legislation and previous research.